‘Dowel’ pinning for feline metacarpal and metatarsal fractures - Zahn, K.; Kornmayer, M.; Matis, U. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
The goal of this retrospective study was to describe dowel pinning, and to compare the results of osteosynthesis and external coaptation of metacarpal and metatarsal fractures in cats. Evaluation of the medical records of 351 cats yielded 63 cats treated with dowel pinning, 35 cats treated with external coaptation and 14 cats treated with both methods within the same limb. All of the cats had been re-evaluated at an average of 2.8 years (six months – 15 years) postoperatively. Dowel pinning was superior to external coaptation when all fractured bones of a limb could be pinned. When internal fixation of multiple fractures was not feasible in all fractured bones due to comminution or fragments that were too short to pin, the outcome was not significantly different from cases treated with external coaptation alone. Malunion was seen in 16% of fractured bones in cats treated with external coaptation and occurred secondary to implant bending in 3% of fractured bones treated with dowel pinning. The latter refers to one operated cat, which had four metacarpal fractures in the same limb. Radiographs taken at re-evaluation showed implant migration within the medullary canal in two cats, although neither showed any signs of non-union or lameness. Non-union was seen in one operated cat, in which the fracture (MC IV) could not be completely reduced with a K-wire. Osteomyelitis did not occur. Dowel pinning is an easy, inexpensive and effective technique for repair of metacarpal and metatarsal fractures in cats.
Keywords: Cat; fracture; metacarpus; metatarsus